A clock regulatory module is required for salt tolerance and control of heading date in rice. (31st August 2021) - Wang, Xiling; He, Yuqing; Wei, Hua; Wang, Lei
Abstract: The circadian clock plays multiple roles in plant stress responses and developmental transition phases. Nevertheless, the underlying molecular mechanisms and individual clock components that coordinately regulate important agronomic traits of rice such as salt tolerance and heading date remain to be elucidated. Here, we identify a rice ternary repressive protein complex composed of OsELF4a, OsELF3‐1 and OsLUX, which was designated as OsEC1 in analogy to a similar complex in Arabidopsis . OsELF4a physically interacts with OsELF3‐1 and OsELF3‐2 in nucleus, whilst OsELF3‐1 rather than OsELF3‐2 strongly interacts with OsLUX, a Myb‐domain containing transcriptional factor. Phenotypic analyses show a role for this complex in heading and salt tolerance. The loss‐of‐function mutants of OsEC1 exhibit lower survival rate under salt stress and late heading date. Transcriptomic profiling together with biochemical assays identified the GIGANTEA homologue OsGI as a direct transcriptional target of OsEC1. Notably, the osgi‐101 mutant, generated by CRISPR/Cas9, is salt tolerant and exhibits early heading date in long day conditions. Together, our findings characterized a transcriptional module in rice composed by the OsEC1 repressing OsGI, which links the circadian clock with salt tolerance and control of heading date. Abstract : To survive on the salinized soil, plants have evolved intricate mechanisms to maintain optimal sodium homeostasis. Nevertheless, the critical genes, which coordinately regulate salt tolerance and control of heading date, remain to be fully characterized in rice. Here, a rice clock ternary repressive complex OsEC1, composed by OsELF4a, OsELF3‐1 and OsLUX, was identified to positively regulate salt tolerance and heading date in rice by directly repressing OsGI transcription. The transcriptional module of OsEC1‐ OsGI may serve as a molecular link to connect the circadian clock with the regulation of salt tolerance and heading date in rice.